Smallholder farmers’ behavioral preferences under the impact of climate change: A comparative analysis of two agricultural areas in China - Peng, Yufang; Xu, Zhengzhong; Wei, Pengbang; Cheng, Linyi (Frontiers in Earth Science, 2022)
Farmers’ behaviors to deal with climate change can be divided into two categories: mitigation and adaptation. Mitigation behaviors can reduce the rate of climate change, while adaptation behaviors can reduce the vulnerability to climate change. In this study, we focused on the factors influencing farmers’ behavioral preferences and explored the differences in their behaviors in response to climate change in different types of regions. A structural equation model was constructed to describe the relationship between trust, risk perception, psychological distance and risk significance, and farmer behaviors. The results indicate that the factors affecting climate adaptation vary greatly in different regions. In agricultural areas, risk salience, psychological distance and mitigation behaviors had a significant influence on farmer adaptation behavior, while risk perception only affects farmers’ mitigation behaviors, and trust can not only predict farmers’ adaptability, but also explain farmers' choice of mitigation behaviors. For farmers in farming and pastoral areas, belief, risk significance level and trust have significant driving effects on both adaptation and mitigation behaviors. The findings provide suggestions for the development of public policy and risk management approaches to deal with climate change, which could encourage active behavior among farmers.